Survival of spray-dried Rhodotorula mucilaginosa isolated from natural microbiota of murta berries and antagonistic effect on Botrytis cinerea - González-Esparza, Alexandra (Array, 2019)
The aim of this study is to evaluate the survival rate and effective antagonistic activity against Botrytis cinerea, responsible for grey mould on harvested fruits and vegetables, of yeast Rhodotorula mucilaginosa, isolated and identified from the natural microbiota of murta (Chilean guava) berries, after spray drying at different inlet air temperatures, mass per volume ratio of encapsulating agent (maltodextrin) and feed flow rates. The 100 % survival of the yeast was obtained after spray drying with 18 % maltodextrin at 130 °C inlet temperature and a feed flow rate of 9.25 mL/min. The dried yeast obtained under such conditions had the highest antagonistic activity in vitro and in vivo on apples, which showed that spray drying is a valid method to produce active dried cells of R. mucilaginosa that can be used for biocontrol of grey mould spoilage. It was also found that the encapsulating agent maltodextrin improved the in vitro antagonistic activity of R. mucilaginosa.